(untitled) (Impetus, 2022)
What this essay seeks is to give an analysis of motor praxiology, defining it, making known what its fields of action and its object of study are. Similarly, what are the central categories of this, the backbone that gives the conceptual support to this science, such as motor tasks, motor situations and motor interactions, giving a brief conception of these in order to open up the logic internal, taking into account that all the previous categories are present within the internal logic, for this reason it is important to mention them at the beginning. Later, already deep in the internal logic, the sport to which the analysis is going to be carried out, will be handball, in this regard, its conformation, basic rules, motor objectives, situations that can happen, roles, among other things will be analyzed. that are of importance.